Guide to business information on Central and Eastern Europe - Konn, Tania. (Aslib/IMI, 2000)
"This guide is an introduction to English language sources, in electronic and print form, dealing with Central and Eastern European business issues. It gives evaluative descriptions and costs of all listed sources, concentrating on recent sources. Sources of information on some of these countries can be difficult to locate, and the author gives guidance on how to go about finding them." "Covers: Albania; Bosnia-Herzegovina; Bulgaria; Croatia; Czech Republic: Hungary; Macedonia; Poland; Romania; Serbia and Montenegro; Slovakia; Slovenia."--BOOK JACKET.